Pentingnya Imunisasi Dasar Pada Bayi Di Kelurahan Bonto Kio Kecamatan Minasatene Kabupaten Pangkep - Sabriana, Riska; Sima, Yenny; Abdullah, Dahlan; Aditia, Donny; Sumampouw, Oksfriani Jufri; Ramli, Rahmat; Rahmat, Rezqiqah Aulia (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
Immunization is an effort to create or actively increase a person's immunity to a disease so that if one day they are exposed to the disease they will not get sick or only experience a mild illness. The specific objectives of this program are to provide information about the importance of immunization for children, to achieve complete basic immunization coverage for infants according to village/kelurahan targets and to achieve advanced immunization targets for children under two years of age (baduta) and elementary school-age children. The method of implementing activities uses the planning stage and the implementation stage. PKM activities in the form of Health Education about Basic Immunization of Infants began with assessment and data collection of the number of families who have babies/toddlers, starting on May 8 2023. Meanwhile the counseling was carried out at Posyandu in the working area of the Minasatene Health Center in Bonto Kio Village, Minasatene District, Pangkep Regency. The results obtained after the implementation of this activity are: 1) increasing parents' knowledge about the importance of basic immunization in infants; and 2) increasing parents' understanding of the side effects that arise after being immunized and how to deal with these side effects.